Atlas of Inherited Retinal Diseases (Advances in Experimental Medicine and Biology, 2018)
This Atlas of Inherited Retinal Disorders provides a thorough overview of various inherited retinal dystrophies with emphasis on phenotype characteristics and how they are related to the most frequently encountered genes. It will also meet the hitherto unmet need of PhD students who would benefit from seeing the phenotypes of the genes they work on and study. Further, because it would help geneticists use and familiarize themselves with the candidate gene approach to test patients' genomes, enabling them to test more efficiently and cost-efficiently (as the cost of genetic testing is quite high and spiralling higher). This invaluable atlas is organized into eight sections starting with the basic knowledge on retinal imaging as an introduction to the subject matter, then diseases are listed according to their inheritance pattern while disorders with extraocular manifestations are grouped by their defining features. This structure will be intuitive to clinicians and students studying IRDs.